2020
DOI: 10.1155/2020/4929053
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Imidazopyridine Derivative Exerts Anticancer Activity by Inducing Mitochondrial Pathway-Mediated Apoptosis

Abstract: Background. Cancer remains a major clinical challenge because of the lack of effective drug for its treatment. To find out novel cancer chemotherapeutic molecules, we explored the anticancer effect of novel imidazopyridine compound 9i and also investigated the underlying molecular mechanism. Methods. Human cervical cancer cell (HeLa) viability was measured by an MTT assay after treatment with compound 9i. Clonogenicity of HeLa cells was investigated by an in vitro colony formation assay. Cell death was visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…The observations by Aliwaini and collaborators [ 15 ] suggest that imidazopyridines may induce apoptosis through p53 regulation. In additions, our results corroborate those of Wang and collaborators [ 13 ], showing that novel imidazopyridine derivatives can exert anticancer activity by inducing mitochondrial pathway-mediated apoptosis and indicating such compounds as promising candidates for glioblastoma treatment [ 46 ] [ 16 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The observations by Aliwaini and collaborators [ 15 ] suggest that imidazopyridines may induce apoptosis through p53 regulation. In additions, our results corroborate those of Wang and collaborators [ 13 ], showing that novel imidazopyridine derivatives can exert anticancer activity by inducing mitochondrial pathway-mediated apoptosis and indicating such compounds as promising candidates for glioblastoma treatment [ 46 ] [ 16 ].…”
Section: Resultssupporting
confidence: 89%
“…These compounds possess a wide spectrum of biological activity and pharmacological properties by binding on different targets [ 11 ]. Therefore, IPs have attracted critical attention due to the interesting properties exhibited in different types of molecular mechanisms in cancer chemotherapy [ 12 ] [ 13 ]. These compounds proved to be potent PI3K/mTOR dual inhibitors with excellent kinase selectivity [ 14 ], inducing cell cycle arrest and apoptosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imidazo[1,2‐ a ]pyridines are bicyclic dinitrogen‐containing privileged scaffolds that have received long‐lasting attention from synthetic and medicinal chemists due to their rich natural abundance and their spectrum of biological activities [1–3] . For example, imidazo[1,2‐ a ]pyridine derivatives exhibit, antiulcer, [2a] anticonvulsant, [2b] antifungal, [2c] antiviral, [2d] anticancer, [2e] antiprotozoal, [2f] antibacterial, [3a] anti‐inflammatory, [2b] anthelmintic, [3b] analgesic, [3c] antitubercular, [3d] antipyretic, [2b] antiepileptic, [3e] and antitumor activities [3f] . Besides, there are several drugs such as zolpidem, [4] alpidem, [4] olprinone, [5] zolimidine, [6] necopidem and saripidem, [7] and rifaximin [8] that contains the imidazo[1,2‐a]pyridine moiety (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Currently, the mitochondrial pathway has been extensively studied as a potential cancer treatment target. [ 13 ] For instance, aloe vera gel polysaccharides induce colon cancer cell death through PINK1/Parkin-mediated mitophagy induced by mitochondrial damage, [ 14 ] while Wang et al [ 15 ] developed a new imidazo [1,2-a] pyridine derivative that exerts anticancer activity by inducing cell apoptosis through the mitochondrial pathway. Studies have reported that defects in mitochondrial-related genes can regulate the tumor immune metabolic microenvironment.…”
Section: Introductionmentioning
confidence: 99%